2015
DOI: 10.1021/acs.chemmater.5b03220
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph-Selective Deposition of High Purity SnS Thin Films from a Single Source Precursor

Abstract: Metal chalcogenide thin films have a wide variety of applications and potential uses. Tin­(II) sulfide is one such material which presents a significant challenge with the need for high quality SnS, free of oxide materials (e.g., SnO2) and higher tin sulfides (e.g., Sn2S3 and SnS2). This problem is compounded further when the target material exhibits a number of polymorphic forms with different optoelectronic properties. Unlike conventional chemical vapor deposition (CVD) and atomic layer deposition (ALD), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 65 publications
11
106
0
Order By: Relevance
“…There are currently five reported or proposed phases, viz. the ground-state orthorhombic Pnma phase, 8 a high-temperature Cmcm phase, 9 and three cubic phases: rocksalt, 10 zincblende, 1113 and the recently reported P 2 1 3 (“π-cubic”) phase with a 64-atom primitive cell. 1417 The sesquisulfide Sn 2 S 3 has also been a source of confusion, as it is relatively easy to prepare and clearly distinguishable from the other tin sulfides 18 yet is frequently predicted to be unstable with respect to decomposition into SnS and SnS 2 in theoretical studies (e.g., as in the current Materials Project 19 entry, mp-1509 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are currently five reported or proposed phases, viz. the ground-state orthorhombic Pnma phase, 8 a high-temperature Cmcm phase, 9 and three cubic phases: rocksalt, 10 zincblende, 1113 and the recently reported P 2 1 3 (“π-cubic”) phase with a 64-atom primitive cell. 1417 The sesquisulfide Sn 2 S 3 has also been a source of confusion, as it is relatively easy to prepare and clearly distinguishable from the other tin sulfides 18 yet is frequently predicted to be unstable with respect to decomposition into SnS and SnS 2 in theoretical studies (e.g., as in the current Materials Project 19 entry, mp-1509 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 A rocksalt-structured phase (Fm3m type) of SnS is accessible under external pressure or epitaxial strain; 9 however, the more recent reports concern thin-films stable under ambient conditions. [10][11][12] To date, this cubic phase has been synthesised using a variety of deposition techniques including aerosol-assisted chemical-vapour deposition (CVD), 13 chemical-bath deposition, 11 and successive ionic-layer adsorption and reaction. 12 The widespread assignment of a zincblende (F43m type) crystal structure to the cubic phase was challenged on the basis of first-principles density-functional theory (DFT) calculations, which demonstrated that this phase was both high in energy and not dynamically stable in finite-temperature molecular-dynamics simulations.…”
mentioning
confidence: 99%
“…14 It was suggested that the observed cubic phase was, instead, related to the rocksalt structure. Nonetheless, assignment of a zincblende phase of SnS continued in the literature, 13 until, recently, a new cubic crystal structure was resolved, using electron and X-ray diffraction, corresponding to a 2×2×2 supercell expansion of the rocksalt structure with large internal distortions. 15 The phase has been named π-SnS (see Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations